Current dependence growth of ZnO nanostructures by electrochemical deposition technique - N. K., Hassan; M. Roslan, Hashim; Yarub, Al - Douri; K. Al - Heuseen (Electrochemical Science Group (ESG), 2013)
Link to publisher's homepage at http://www.electrochemsci.org/